The Current Landscape of Molecular Pathology for the Diagnosis and Treatment of Pediatric Medulloblastoma - Alayna Koch; Ashley Childress; Emma Vallee; Alyssa Steller; Scott Raskin (Journal of Molecular Pathology)
Medulloblastoma (MB) is a malignant brain tumor that requires intense multimodal treatment. There is significant treatment-related morbidity associated with MB, and overall prognosis varies between the subgroups of the disease. These tumors were previously risk-stratified based solely on histopathological features. However, advancements in oncologic molecular research have led to novel changes to MB tumor classification, which also affects the prognosis and treatment strategies for individual patients. The WHO CNS5 now recognizes four main molecular subgroups of MB. Each subgroup contains its own genomic heterogeneity that correlates with a unique way to risk stratify patients, determine overall prognosis, and inform treatment. These discoveries have already impacted the implications and outcomes of current treatments based on the subgroup of patients. Ongoing research to better understand this classification system has paved the way for the development of molecular targeted therapy.